RELATION BETWEEN SELECTED WEATHER FACTORS AND INSURANCE INDEMNITY IN UKRAINIAN AGRICULTURE - Klapkiv, Lyubov; Kedra, Arleta (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
The present paper is devoted to examining if weather variables have a significant impact on the level of indemnity in examined agriculture insurances, i.e. insurance of winter crops. The authors will determine whether indicators as excessive rainfall and extreme temperatures (especially frost) contribute to crucial increase of insurance indemnity. According to currently existing theories, weather changes have vital consequences both for farmers and for insurers as they take over the risk. The goal of the present paper is to analyse strength and direction of correlation between weather variables and insurance indemnity in case of winter plants to state whether these influence amounts of money paid to farmers for their crops’ losses.